Tissue injury characterization by pre-contrast T1 mapping post myocardial infraction - Mohd Shah, Azarisman Shah; Li, Andrew; Wong, Dennis T.; Richardson, James D.; Chua, Seng Keong; Samaraie, Luay; Sidharta, Samuel L; Glenie, Timothy; Williams, Kerry; Koschade, Ben; Teo, Karen; Worthley, Matthew; et al. (Society for Cardiovascular Magnetic Resonance (SCMR), 2013)
Background Myocardial scar and edema can be assessed by late gadolinium enhancement (LGE) and T2W cardiac magnetic resonance (CMR) respectively, but each has important limitations. T1-mapping has emerged as an alternative method to characterize acute ischemic injury and contemporary mapping sequences make this clinically feasible. We assessed the T1 relaxation time in myocardial segments exhibiting varying degrees of ischemic injury in patients after acute MI.